The Characteristics and Consequences of Serial Sex Offenders’ Actions: the Example of Ukraine - Spytska, Liana (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
Serial sexual crimes are considered highly dangerous and have lasting effects on both victims and society. As such, the importance of investigating and preventing these crimes is increasingly recognised, with particular attention given to forensic analysis and the study of the perpetrators’ modus operandi. The purpose of this study was to explore the characteristics of serial sexual offences, their unique features, and the consequences for both the victims and the society, based on Ukrainian experiences. The study employed methods such as analysis, generalisation, and the normative-dogmatic method. The findings indicate that serial sexual offenders can be classified based on their methods of attack into two main categories: the “stranglers” and the “butchers.” These groups differ in their approach, motivations, and the nature of the offences. The study also identified four key psychological profiles of serial sexual offenders: “Power–Calming”, “Power–Affirmation”, “Anger–Vengeance”, and “Anger–Arousal”, with each of them representing different motivations behind the crimes. Additionally, the study examined the concept of modus operandi and ritualistic elements in serial sexual crimes, which play a crucial role in understanding the criminal’s profile, motives, and behavioural patterns. The research emphasises the need for developing investigative profiles that consider factors such as location, time of the crime, weather conditions, and movement patterns of victims and perpetrators. Moreover, the study identified significant gaps in Ukraine’s legal framework regarding serial sexual offences, highlighting the need for specialised legislation. The consequences of these crimes for victims and the society are profound, underscoring the necessity for a multi-faceted approach to prevention, including education, psychological support, and enhanced cooperation between various societal sectors. The study’s findings can inform public awareness campaigns and contribute to the development of strategies to reduce the incidence of serial sexual crimes.